2012
DOI: 10.1371/journal.pone.0047760
|View full text |Cite
|
Sign up to set email alerts
|

The Apolipoprotein E (APOE) Gene Appears Functionally Monomorphic in Chimpanzees (Pan troglodytes)

Abstract: BackgroundThe human apolipoprotein E (APOE) gene is polymorphic, with three primary alleles (E2, E3, E4) that differ at two key non-synonymous sites. These alleles are functionally different in how they bind to lipoproteins, and this genetic variation is associated with phenotypic variation for several medical traits, including cholesterol levels, cardiovascular health, Alzheimer’s disease risk, and longevity. The relative frequencies of these alleles vary across human populations, and the evolution and mainte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 63 publications
1
52
0
1
Order By: Relevance
“…We also note that from an evolutionary point of view, the ApoE4 genotype is apparently present only in the primate line, including ancestors to humans 59, implying that the maintenance of the ε4 allele in this genus may actually confer a selective advantage. Besides the aforementioned role of ApoE4 in apoptosis 20 (a MAM‐mediated function 60), another possible advantage might be in resistance to infection 61, 62.…”
Section: Resultsmentioning
confidence: 83%
“…We also note that from an evolutionary point of view, the ApoE4 genotype is apparently present only in the primate line, including ancestors to humans 59, implying that the maintenance of the ε4 allele in this genus may actually confer a selective advantage. Besides the aforementioned role of ApoE4 in apoptosis 20 (a MAM‐mediated function 60), another possible advantage might be in resistance to infection 61, 62.…”
Section: Resultsmentioning
confidence: 83%
“…ApoE is a polymorphic protein with common variants known as E2, E3, and E4 that are encoded by the ε2, ε3, and ε4 alleles, respectively, with population frequencies of approximately 8, 77 and 15%, respectively [97][98][99]. ApoE4 has been confirmed as an important factor for dementia and progress of cognitive impairment in the elderly [100,101].…”
Section: Insulin Resistance and The Apoe ε4 Allelementioning
confidence: 99%
“…Even after the evolution of other alleles, ε4 remained present in our ancestors, given that McIntosh et al [67] showed that the Denisovan hominin (30 000–80 000-years old) appears to have had the ε4 allele. Although direct measures of lipid binding have not been assessed, living chimpanzees have a form of the APOE gene that is believed to be functionally similar to the human APOE ε3 allele based on amino acid predictions, and the chimpanzee APOE amino acid sequence is monomorphic [67], suggesting the ε4 allele was an evolutionary novelty during human evolution (Box 2). …”
Section: Apoe Evolutionmentioning
confidence: 99%